EDN1 and NTF3 in keloid pathogenesis: computational and experimental evidence as novel diagnostic biomarkers for fibrosis and inflammation - Gong, Hui; Liu, Jing; Chen, Nanji; Zhao, Hengguang; He, Bailin; Zhang, Hongpei; Wang, Wenping; Tian, Yi (Frontiers in Genetics, 2025)
ObjectiveTo investigate the roles of oxidative stress-related differentially expressed genes (OSRDEGs) in keloid formation and explore their potential value in diagnosis and treatment.MethodsGene expression data from the GEO database, including GSE145725 and GSE44270 as training sets and GSE7890 as a validation set, were utilized. OSRDEGs were identified, followed by Weighted Gene Co-expression Network Analysis (WGCNA), GO/KEGG enrichment analysis, and Gene Set Enrichment Analysis (GSEA). Key genes were further screened through protein-protein interaction (PPI) network analysis and receiver operating characteristic (ROC) curve analysis. miRNA targets, transcription factors (TF), and potential drug targets of these genes were predicted. Immune cell infiltration analysis was performed to assess the association between OSRDEGs and immune cells, which was validated using GSE7890. Finally, the expression of key genes was experimentally validated using quantitative PCR (qPCR), immunohistochemistry (IHC), and hematoxylin-eosin (HE) staining.ResultsA total of 13 OSRDEGs were identified. WGCNA and functional enrichment analyses revealed that these genes were primarily involved in fibrosis and inflammatory processes in keloids, such as the MAPK signaling pathway, lymphocyte and monocyte proliferation, and inflammatory pathways involving IL-18 and IL-23. PPI network analysis, ROC analysis, and immune infiltration results identified Endothelin-1 (EDN1) and Neurotrophin-3(NTF3) as key genes with high sensitivity and specificity. These genes were positively and negatively correlated with activated mast cells, respectively, suggesting their dual regulatory roles in fibrosis and inflammation. External dataset validation, qPCR, correlation analysis, HE staining, and IHC results demonstrated that EDN1 and NTF3 were highly expressed in keloid tissues and were associated with excessive collagen deposition and immune cell infiltration.ConclusionEDN1 and NTF3, as OSRDEGs, play critical roles in the pathogenesis and progression of keloids. They may contribute to fibrosis and inflammation through the regulation of oxidative stress, the MAPK signaling pathway, and mast cell activation. These findings highlight EDN1 and NTF3 as potential diagnostic biomarkers and therapeutic targets, providing novel insights into the pathogenesis and treatment strategies for keloids.